Premedication in Supravaginal Uterine Amputation in Menopausal Women - D. V Sadchikov; U. V. Stolyarova; T. S. Vartanyan (Общая реаниматология)
Objective: to study the efficiency of using small-dose estrogens as a component of remedial premedication. Subjects and materials. A hundred and ninety menopausal women were examined. All the patients were divided into a study group and a control one. Group 1 included patients with uterine myoma and menopausal syndrome, which was further divided into two subgroups: Subgroup A comprised patients who as a remedial premedication, along with the standard therapy, received hormonal therapy with oral estradiol in a dose of 2 mg once daily for 7 days. There were no contraindications to the use of these drugs in all the women from this subgroup. Postoperative estrogen therapy was continued in the above doses for a year (as recommended by the International Menopause Committee). Subgroup B consisted of 40 women with menopausal syndrome who received the standard conventional premedication and postoperative therapy. Group 2 included 70 patients with physiological menopause and uterine myoma. Studies were made when remedial premedication was given just before surgery and on discharge from hospital on days 7—8. Results. In the patients with the menopausal syndrome, the level of follicle-stimulating hormone (FSH) was ascertained to be higher than that in women with normal menopause, the level of estradiol was accordingly lower. The differences found in the levels of hormones in the patients depending on the clinical course of a menopausal period allowed the use of hormonal replacement therapy with estradiol in the remedial premedication regimen as both etiologically and pathogenetically founded. On admission, the first stage of psychoemotional testing before remedial premedication revealed impairments of memory, attention, and thinking, as well as high anxiety in all the patients with myoma and menopausal syndrome. There was a significant reduction in long-term memory and memorization. Seven days after preoperative preparation using estradiol, 2 mg/day, there were no short- and long memory disorders and there was stabilization of psychoemotional disorders in most patients. Hemodynamic studies showed that before remedial premedication the patients with abnormal menopause had the following hemodynamics types: hypertensive-hypodynamic dissociation (60.2%) and isolated hypertension (25.2%). In patients with concomitant menopausal syndrome, correction of hemodynamic changes, with the type of central hemodynamics being kept in mind, reduced the frequency of a hypertensive-hypodynamic dissociation and isolated hypertension to 24.7 and 12.0%, respectively. Conclusion. Evaluation of the efficiency of preoperative preparation of patients with concomitant menopausal syndrome may lead to the conclusion that there are benefits of using small doses (2 mg/day) of estrogen for 5—7 days as a component of remedial premedication. By exerting a specific hormonal effect, estrogen therapy promotes psychoemotional stabilization and cardiovascular function normalization. This all reduces the time of preparation of patients for surgery, leads to its favorable course, and decreases the incidence of postoperative complications. Key words: premedication, uterine myoma, menopausal syndrome, psychoemotional disorders, hemodynamics, estrogens, preoperative preparation.